2005
DOI: 10.1016/j.mito.2005.01.004
|View full text |Cite
|
Sign up to set email alerts
|

17β-estradiol stimulates MAPK signaling pathway in human lens epithelial cell cultures preventing collapse of mitochondrial membrane potential during acute oxidative stress

Abstract: Abstract17β-estradiol (17β-E 2 ) protects against H 2 O 2 -mediated depletion of intracellular ATP and lessens the degree of depolarization of mitochondrial membrane potential (Δψ m ) in cultured lens epithelial cells consequential to oxidative insult. We now report that 17β-E 2 acts as a positive regulator of the survival signal transduction pathway, MAPK which, in turn, acts to stabilize Δψ m , in effect, attenuating the extent of depolarization of mitochondrial membrane potential in the face of acute oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…These signaling events can be altered by THC (Howlett, 2005;Demuth and Molleman, 2006) and can be involved in both the mitochondrial effects of toxicants (Moor et al, 2005;Chen et al, 2006;Oh et al, 2006;Zhou et al, 2006;Zhang et al, 2007) and in the regulation of chemotaxis (Phillips et al, 2003). Using the same serum stimulation conditions as those employed in our chemotaxis assays, time-dependent phosphorylation of the IkB-a, Erk-MAPK, p70S6K, CREB, STAT3, STAT5, and JNK signaling proteins was observed with only p38 failing to show exposure-dependent phosphorylation.…”
Section: Discussionmentioning
confidence: 66%
“…These signaling events can be altered by THC (Howlett, 2005;Demuth and Molleman, 2006) and can be involved in both the mitochondrial effects of toxicants (Moor et al, 2005;Chen et al, 2006;Oh et al, 2006;Zhou et al, 2006;Zhang et al, 2007) and in the regulation of chemotaxis (Phillips et al, 2003). Using the same serum stimulation conditions as those employed in our chemotaxis assays, time-dependent phosphorylation of the IkB-a, Erk-MAPK, p70S6K, CREB, STAT3, STAT5, and JNK signaling proteins was observed with only p38 failing to show exposure-dependent phosphorylation.…”
Section: Discussionmentioning
confidence: 66%
“…E 2 activates (i.e., phosphorylates) ERK and stabilizes mitochondrial membrane potential when human and GSH-depleted bovine lens cells are exposed to H 2 O 2 stress (28). The work of Moor et al (28) established a correlative association between estradiol-stimulated activation of the MAPK signaling pathway and protection of mitochondrial membrane potential in an ocular cell culture model.…”
mentioning
confidence: 99%
“…All experiments were performed with monolayers of HLE-B3 cells that did not exceed passage 22 (5). To deplete the cell cultures of estrogens, cells were maintained in 20% charcoal dextran-stripped FBS (CSFBS; Gemini Bio-Products, Woodland, CA) MEM for 24 -48 h then switched to 2% CSFBS MEM for 18 h with a final medium change to serum-free MEM on the day of the experiments as described previously (28). In select experiments, cells were pretreated with estrogen overnight with 2% CSFBS in MEM followed by a medium change to 0.5% (CSFBS) MEM for 12-18 h with the addition of fresh estrogen the next morning before experimentation.…”
mentioning
confidence: 99%
“…The association of oestradiol with mitochondria has been recently confirmed by Camarata et al, 9 with oestrogen receptors being shown on the mitochondrial membrane. The rapid and non-genomic action of oestrogen against acute oxidative stress has been recently shown by Moor et al, 11 wherein oestradiol activates an important antiapoptotic pathway within 15 min of administration. The protective effect of oestradiol mediated by preventing the LECs from undergoing apoptosis is evident from the comet analysis in this study.…”
Section: Eyementioning
confidence: 92%
“…8 The precise mechanism of these cytoprotective effects of oestrogen against H 2 O 2 in lens epithelial cells (LECs) is not known, but a plethora of cellular responses to the steroid has been reported, including the protection of the mitochondrial function, stimulation of antiapoptotic proteins, and stimulation of protective signalling pathways. [9][10][11] Wang et al 12 have demonstrated that oestrogens are potent cytoprotectants that preserve the mitochondrial function during H 2 O 2 -induced oxidant insult. Nevertheless, the exact mechanism of oestrogen action against oxidative stress is not known.…”
Section: Introductionmentioning
confidence: 99%